2006
DOI: 10.1016/j.jfms.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against feline coronavirus andChlamydophila felisin Swedish cats

Abstract: Serum samples from 214 Swedish cats with no signs of infectious disease were analysed for the presence of antibodies against Chlamydophila felis (Cp felis), while 209 of these were also analysed for feline coronavirus (FCoV) antibodies. The prevalence of antibodies against Cp felis was 11%, with no significant difference between purebred and mixed breed cats. The overall prevalence of antibodies against FCoV was 31%, significantly higher among pure breed cats (65%) than among mixed breed cats (17%). A high pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 14 publications
(22 reference statements)
5
29
3
Order By: Relevance
“…Our results are on contrary with other studies reported 37.3% in male and 56.1% female cats in UK (7) and 25% in male and 35% in female in Swedish cats (8). The prevalence of FeLV infection was detected in female cats 6.1% and in male cats 10%.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are on contrary with other studies reported 37.3% in male and 56.1% female cats in UK (7) and 25% in male and 35% in female in Swedish cats (8). The prevalence of FeLV infection was detected in female cats 6.1% and in male cats 10%.…”
contrasting
confidence: 99%
“…FCoV is mainly transmitted by fecal-oral route that is more frequent in younger cats than in adult cats (8,13). Additionally, FeLV has been found commonly in younger colony cats (12).…”
mentioning
confidence: 99%
“…However, in England and Sweden, only 9.1% and 11% of the animals, respectively, were IFA-positive (Gunn-Moore et al 1995, Holst et al 2006. Among unvaccinated cats with clinical signs (G2), 68.89% (31/45) were IFApositive, as also reported by Wills et al (1988), who found 60% (69/116) of IFA-positive animals.…”
Section: Virus Reviews and Research 15 Nr 2 2010mentioning
confidence: 53%
“…The presence of complement-fixation antibodies in cat sera ranged from 0 to 12.7% (Studdert & Martin 1970, Studdert et al 1981, Povey & Johnson 1971, Lazarowicz et al 1982, Fukushi et al 1985. Indirect immunofluorescence assay (IFA) in English and Swedish cats with clinical signs showed antibody titers ranging from 9.1% to 11%, respectively (Holst et al 2006;Gunn-moore et al 1995). In contrast, 45% of healthy cats in England were positive in IFA (Gethings et al 1987).…”
Section: Virus Reviews and Research 15 Nr 2 2010mentioning
confidence: 99%
“…A similar pattern was observed in a previous study that also examined the M gene (CHANG; EGBERINK; ROTTIER, 2011) which determined that FIPVs originate from FECVs by the accumulation and selection of point mutations (POLAND et al, 1996;VENNEMA et al, 1998;PEDERSEN et al, 2009). The internal mutation hypothesis has been widely accepted and is mainly supported by the close similarities between FECoV and FIPV and the low incidence of FIP outbreaks, despite the high proportion of FCoV-seropositive cats (SPARKES; GRUFFYDD-JONES; HERREWEGH et al, 1997;HOLST et al, 2006;PRATELLI, 2008).…”
Section: Discussionmentioning
confidence: 99%